Patterns of Recurrence and Outcome According to Breast Cancer Subtypes in Lymph Node–Negative Disease: Results From International Breast Cancer Study Group Trials VIII and IX - Metzger-Filho, Otto (American Society of Clinical Oncology, 2013)
PURPOSE: To retrospectively evaluate the pattern of recurrence and outcome of node-negative breast cancer (BC) according to major subtypes. PATIENTS AND METHODS: In all, 1,951 patients with node-negative, early-stage BC randomly assigned in International Breast Cancer Study Group Trials VIII and IX with centrally reviewed pathology data were included. BC subtypes were defined as triple negative (TN; n = 310), human epidermal growth factor receptor 2 (HER2) positive (n = 369), and hormone receptor positive with high (luminal B–like [LB-like]; n = 763) or low (luminal A–like [LA-like]; n = 509) proliferative activity by Ki-67 labeling index. BC-free interval (BCFI) events were invasive BC recurrence in local, contralateral breast, nodal, bone, or visceral sites. Time to first site–specific recurrence was evaluated by using cumulative incidence and competing risks regression analysis. RESULTS: Median follow-up was 12.5 years. The 10-year BCFI was higher for patients with LA-like (86%) BC compared with LB-like (76%), HER2 (73%), and TN (71%; P < .001) BC. TN and HER2 cohorts had higher hazard of BCFI event in the first 4 years after diagnosis (pre-trastuzumab). LB-like cohorts had a continuously higher hazard of BCFI event over time compared with LA-like cohorts. Ten-year overall survival was higher for LA-like (89%) compared with LB-like (83%), HER2 (77%), and TN (75%; P < .001) BC. LB-like subtypes had higher rates of bone as first recurrence site than other subtypes (P = .005). Visceral recurrence as first site was lower for the LA-like subgroup, with similar incidence among the other subgroups when treated with chemotherapy (P = .003). CONCLUSION: BC subtypes have different distant recurrence patterns over time. Defining different patterns of BC recurrence can improve BC care through surveillance guidelines and can guide the design of clinical studies.